Panorama da autoavaliação institucional nos Institutos Federais de Educação, Ciência e Tecnologia: uma meta-avaliação de perspectiva emancipatória - Oliveira, Ivan dos Santos (Universidade Federal de São Carlos, 2023)
The evaluation of Brazilian higher education takes place in a context in which neoliberal policies are hegemonic, conferring a character of regulation and control to the evaluation processes. Nevertheless, the formulation and implementation of the National Higher Education Assessment System (SINAES) constituted an attempt to give an emancipatory character to the assessment of subjects and Higher Education Institutions (IES), through Institutional Assessment, more precisely, through internal evaluation. In this sense, the present research had as general objective: to understand and characterize the processes of institutional self-evaluation in the Federal Institutes of Education, Science and Technology, considering the emancipatory aspects of the evaluation, in order to identify the levels of attendance of the observable emancipatory aspects in these processes. As for its nature, the research was characterized as qualitative and as for the type, it fits as an exploratory-descriptive study. The materials analyzed were the final institutional self-assessment reports of the 2018-2020 evaluation cycle of 13 Federal Institutes of Education, Science and Technology. In Paulo Freire (1986, 1987, 1995, 2001, 2002, 2014) we base our vision of the world and of education that is opposed to neoliberal rationality; in Saul (2010) we base the concept of Emancipatory Evaluation and in Dias Sobrinho (2003) and other authors, we systematize the fundamentals of Institutional Evaluation from a democratic-subjectivist perspective, from which we list the categories that characterize an emancipatory institutional self-evaluation practice and that served basis for the construction of an analytical and metaevaluation instrument of emancipatory aspects, together with the theoretical-practical framework of summative meta-evaluation, in the perspective of Stufflebeam (2001) and Scriven (2009). In this way, 14 parameters of emancipatory aspects were elaborated, which are interrelated, being 11 of merit (Dialogicity, Participation, Plurality, Negotiation, Globality, Formativity, Comparability, Legitimacy, Identity and Mission, Commitment, Publicity) and 3 of value (Self-knowledge, Critical-Transforming Potential, Applicability or Relevance). As a result, we found that the processes of institutional self-assessment in Federal Institutes are complex, in the sense that these assessments express and recognize either a formative perspective of assessment for the emancipation of subjects and institutions, or an assessment perspective aligned with neoliberal rationality, however, with predominance of the latter perspective. The analysis of the merit and value parameters established by this research revealed that the meta-assessed self-assessment experiences mostly failed to meet the ethical, political and democratic aspects of the assessment, but did meet other aspects, even if partially. Thus, it was possible to verify that the meta-assessed self-assessment experiences showed, in general, a predominance of partial compliance with the emancipatory aspects of the assessment, which confirmed our initial hypothesis that the processes of institutional self-assessment in the Federal Institutes of Education, Science and Technology are not emancipatory.
Overview of institutional self-evaluation in the Federal Institutes of Education, Science and Technology: a metaevaluation from an emancipatory perspective
Panorama de la autoevaluación institucional en los Institutos Federales de Educación, Ciencia y Tecnología: una metaevaluación desde una perspectiva emancipadora
Keywords: Autoavaliação institucional; Avaliação emancipatória; Meta-avaliação; Institutos Federais; Institutional self-assessment; Emancipatory assessment; Metaevaluation; Federal Institutes of Education, Science and Technology; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL